Importance of micro-watershed studies: Cintra stream micro-watershed model - Belluta, Ivalde [UNESP]; Silva, Assunta Maria Marques da [UNESP]; Valente, José Pedro Serra [UNESP] (My University, 2010)
Water quality in the Cintra Stream micro-watershed was assessed by means of analyses during 2 periods (June/2005-May/2006 and January/2007-December/2007), using bimonthly collections at 8 different sites, for the physical and chemical variables pH, NO3-, NO2-, BOD 5, DO and TOC. This work aimed to study the anthropogenic effects on the Cintra Stream and their interrelations with soil occupation, polluting sources, water use and contributions to the water quality of two large bodies of water: the Tietê River and the Guarani Aquifer. To study the variables, variance analyses were followed by Tukey’s test, at a 5% significance level. All studied parameters indicated that the stream shows self-depuration capacity starting at site 3 due to dilution, oxygenation of the water and consequent biodegradation of the existent organic matter. Corrective measures at sites 1 and 2 followed by preventive actions in agricultural areas (S3 to S7 ) will permit use of the stream water in the rural area.

Fue evaluada la calidad del agua de la cuenca del arroyo de Cintra a través de análisis en 2 periodos (junio/2005 a mayo/2006 y enero a diciembre/2007), con colectas bimestrales en 8 puntos distintos con las variables físicas y químicas pH, NO3-, NO2-, DBO 5, OD y COT. Este trabajo se propuso estudiar los efectos antropogénicos en el arroyo de Cintra y sus interrelaciones con la ocupación del suelo, fuentes contaminantes, uso del agua y contribuciones para la calidad de las aguas de dos grandes cuerpos de agua: Río “Tietê” y Acuífero “Guaraní”. Para analizar las variables, fueron realizadas análisis de varianza seguidas del Test de Tukey, con un nivel de significancia de p<0,05. Todos los parámetros estudiados demostraron la capacidad de autodepuración del arroyo a partir del punto 3 debido al efecto de dilución, oxigenación del agua y consecuente biodegradación de la materia orgánica existente. Medidas correctivas en los puntos 1 y 2,seguidas de acciones preventivas en áreas agrícolas (del P3 al P7 ) posibilitarán el uso del agua del arroyo en el área rural. P
Importancia del estudio de las cuencas hidrográficas: una microcuenca modelo del arroyo de Cintra
Keywords: Micro-watershed; Cintra stream; Tietê river; Guaraní aquifer; Physicochemical parameters; Microcuenca hidrográfica; Arroyo de Cintra; Río Tietê; Acuífero Guaraní; Parámetros físico-químicos